2014
DOI: 10.1111/bcp.12289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the reduction of calcineurin inhibitors on renal function in heart transplant patients: a systematic review and meta‐analysis

Abstract: AIMSCalcineurin inhibitors (CNIs) taken after heart transplantation lead to excellent short-term outcomes, but long-term use may cause chronic nephrotoxicity. Our aim was to identify, appraise, select and analyse all high-quality research evidence relevant to the question of the clinical impact of CNI-sparing strategies in heart transplant patients. METHODSWe carried out a systematic review and meta-analysis of randomized controlled trials on CNI reduction in heart transplant recipients. Primary outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The target MMF dose was 2000-3000 mg/day. All patients received corticosteroids (minimum 0.1 mg/kg during months 1-3 and 0.05-0.1 mg/kg during months [4][5][6][7][8][9][10][11][12].…”
Section: Study Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The target MMF dose was 2000-3000 mg/day. All patients received corticosteroids (minimum 0.1 mg/kg during months 1-3 and 0.05-0.1 mg/kg during months [4][5][6][7][8][9][10][11][12].…”
Section: Study Treatmentmentioning
confidence: 99%
“…Posttransplant renal deterioration is multifactorial in etiology, with pretransplant renal dysfunction (2,4), older age (2) and comorbidities such as diabetes (2,4) known to contribute, but long-term calcineurin inhibitor (CNI) therapy also plays an important role (3,5). A recent meta-analysis of randomized controlled trials in de novo and maintenance heart transplant patients found that reducing CNI exposure significantly improved posttransplant renal function (6).…”
Section: Introductionmentioning
confidence: 99%
“…These controversial results for CNI reduction were also confirmed in the meta‐analysis of eight open‐label studies (n = 723). Overall, CNI reduction did not have any favorable effect on the renal function at 12 months follow‐up …”
Section: Cni Reductionmentioning
confidence: 86%
“…Therefore, renal protection strategies are warranted to further improve patients' outcomes after HTx. 5,6 Renal dysfunction after HTx is derived from preoperative, intraoperative, and post-operative factors. Among the post-operative factors, the use of calcineurin inhibitors (CNIs) has a marked effect on renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Renal dysfunction is frequently observed prior to HTx and typically followed by a progressive decline over time after HTx, 2–4 which contributes late mortality in HTx recipients. Therefore, renal protection strategies are warranted to further improve patients' outcomes after HTx 5,6 …”
Section: Introductionmentioning
confidence: 99%